A Simple Methodology for Monitoring and Analysis of Vertical Displacement of Buildings - El-Ashmawy, Dr. Khalid L. A. (American Scientific Research Journal for Engineering, Technology, and Sciences, 2019)
Measurements and monitoring of the engineering structures such as buildings provides information about the health of the structures and their safety aspects as well the safety of the public. This paper explains the development of a method for the monitoring and analysis of vertical deformation of buildings. The proposed method is developed to add a new solution to traditional methods of geometric leveling, leveling routing, least squares technique for level network adjustment and analysis, and global statistical analysis for evaluating the vertical displacement. The proposed method was used for monitoring and analyzing the vertical displacement of official building in Cairo, Egypt. Three local reference stations, five auxiliary points, and twenty monitoring points were used. All measurements were taken using an automatic level with a parallel plate micrometer attachment and a geodetic invar staff. The observations were carried out at eight epochs of one-month interval. Observations were adjusted using least squares adjustment technique to determine the adjusted levels, observations and generating the necessary statistical data. The results of the first epoch were used as reference results such that the subsequent epochs values were compared with them to compute the vertical displacement of monitoring points for each epoch. Furthermore, values of vertical displacement were compared with their corresponding computed 95% confidence intervals to determine the significance of the existing displacement. The results showed the stability of the building during the monitoring period. The case study shows the efficiency of geometric leveling for the monitoring of deformation of the building structures. It is strongly recommended that engineering structures especially high rise buildings should be monitored at regular basis to check their stability and thereby increasing their safety.